Asian Segregation and Scholastic Achievement: Evidence from Primary Schools in New York City - Rocco D'Este; Elias Einiö (Institute of Labor Economics (IZA), 2018)
This paper examines the effects of Asian segregation on students' academic performance in New York City primary schools. We use exogenous variation in the share of Asian students across cohorts and schools stemming from a fertility shock among Asian population in the Chinese year of the Dragon. A one-percentage-point increase in Asian student share reduces non-Asian math and ELA scores by 0.03 and 0.05 standard deviations. The effects are largest among black and Hispanic students. We find little evidence of effects among white students. The findings suggest that desegregation policies may generate net benefits in terms of student achievement.
Keywords: I20; I29; J15; 330; segregation; primary education; Chinese Dragon year; ethnicity; student achievement; public schools; test score; student composition; Asian students; race